'Doubly deprived': a post-death qualitative study of primary carers of people who died in Western Australia - Keesing, Sharon; Rosenwax, Lorna; McNamara, Beverley (Blackwell Publishing, 2011)
This paper explores the daily experiences and occupational needs of family carers of people who were dying, with particular reference to their daily routines and ability to undertake other varied activities during the period of care. The impact of the caring experience on these occupations was then examined to determine how, and if, these occupational needs were addressed in the community using potential and available services. An exploratory approach using grounded theory was employed to examine these experiences. Participants were recruited from metropolitan (n = 10) and rural (n = 4) locations across Western Australia between February and June 2009, using a purposive sampling method. A semi-structured interview guide was developed following consultation with the literature, expert opinion and piloting. Interviews were conducted in participants’ homes and questions were asked about their experiences as a carer including routines, engagement in usual activities and the impact of the caring role on their daily life during and after the period of care.Each interview was transcribed verbatim and analysed to determine potential themes. Two important themes were identified: (1) Carers experienced disengagement and deprivation from their usual occupations during and after the period of care; and (2) Participants described significant disempowerment in their role as carer. Carers are ‘doubly disadvantaged’ as a result of their caring role; they are unable to participate in their usual occupations and they are not recognised for their contributions as carers. Carers experienced disengagement and deprivation from their usual occupations, contributing to physical, psychological and emotional difficulties and this may result in long term consequences for health and well-being. In addition, the current services and support available for carers in the community are deemed inadequate; placing further stress on a health care system which needs to cope with increasing demands as a result of the ageing population in Australia.